APPLICATION OF BUDDHIST PRINCIPLES : HEART OF A MILLIONAIRE FOR LIVING IN THE DIGITAL AGE - Sooksai, Rattikarn; ., Phrakru Wijitsreerajal; ., Phrakru Kositwattananukul; Panasree, Sitthichok (Journal of MCU Nakhondhat, 2024)
This article is an analysis of the application of the principles of the Millionaire's Heart for living in the digital age. Living according to the principles of the heart of a millionaire in the digital age. It is important and necessary for people in today's era. Because it will enable users of such principles to succeed in their daily lives, and have a good plan for living in this digital age. The heart of a millionaire can also be called the four benefits of Ditthadhammikattha, namely u-ar-ka-sa. U is an abbreviation for Utthana Sampada, AR is an abbreviation for Arakkha Sampada, ka is an abbreviation for Kalyanamittata, and SA is an abbreviation for Samachivita. The details of appliying of the principles are as follows: 1) Utthana Sampatha: Living your life with diligence and orderly lifestyle, having the intelligence to do many things until you have expertise in work that makes the job easy to complete. 2) Arakkha Sampatha: Knowing how to protect wealth earned by knowing the value of various things and knowing what is necessary in life. What is desire because of one's desires? 3) Kalyanamittata: having an understanding of friendship. Knowing how to distinguish between good people and bad people. Choose to associate with good people. Know how to maintain oneself. Negotiate with people in the village or community in a friendly manner. and 4) Samachivittha, living life with sufficiency. Knowing the way to gain wealth and the way to its depletion or depletion. Make a suitable living, don’t waste money, and don't let it get too irritating. Knowing that expenses must not exceed the income received.